Latin Aphorisms and Phrases in the Deontological Didactics of Romanian - Eugenia MINCU; Dorina MACOVEI (ACROSS)
Latin aphorisms and expressions constitute a form of human didactics.  The present article is about Latin idiomaticity related to the didactics of Romanian as a foreign language. Teaching-learning lessons of the Romanian language and medical terminology, in alloglot classes, are important in the formation of a linguistic-terminological axis (which will ensure a later integration of the doctors in the socio-professional environment), but also of a respectful attitude towards the Romanian language. Deontological didactics (deontology is considered ‘the science of moral duties and obligations’) is based on the concepts of goodness and beauty, which are aesthetic categories that provide the basis for general human norms of behaviour and cultivate the qualities of bonhomie. These two aesthetic categories, goodness and beauty, are likely to be cultivated in the Romanian language teaching/learning classes, with Latin aphorisms and expressions as reference points. For example, the feelings of: respect - Pulchra res homo est si homo est/A human being is beautiful if he is human, etc.; tolerance - De gustibus et coloribus non disputandum/ Tastes and colours are not discussed/There is no accounting for taste(s); moderation - Si tacuisses, philosŏphus mansisses/Had you kept silent, you would have remained a philosopher, etc.; Medice, cura aegrotum, sednon morbum/Cure the man, not the disease - the aphorism emphasizes the personality of the patient, which matters for the doctor's attitude.